How the Electoral College Influences Campaigns and Policy: The Probability of Being Florida - Strömberg, David (American Economic Review, 2008)
This paper analyzes how US presidential candidates should allocate resources across states to maximize the probability of winning the election, by developing and estimating a probabilistic-voting model of political competition under the Electoral College system. Actual campaigns act in close agreement with the model. There is a 0.9 correlation between equilibrium and actual presidential campaign visits across states, both in 2000 and 2004. The paper shows how presidential candidate attention is affected by the states' number of electoral votes, forecasted state-election outcomes, and forecast uncertainty. It also analyzes the effects of a direct national popular vote for president. (JEL D72)